IMPROVEMENT OF LEGAL, MANAGEMENT AND FINANCIAL ASPECTS ON “SUKSES BERSAMA” BUMDES IN PEJATEN VILLAGE, KRAMATWATU DISTRICT, SERANG REGENCY - Asnawi Asnawi; Encep Saefullah; Ina Khadijah (International Journal of Engagement and Empowerment, 2022)
Partners in the Stimulus Community Partnership Program (PKMS) are the Pejaten Village Government and the manager of the Village-Owned Enterprises (BUMDes) "Sukses Bersama" in Pejaten Village, Kramatwatu District, Serang Regency, Banten Province. The objectives of this Community Service Activity Stimulus Community Partnership Program (PKMS) are (1), to provide legal assistance related to the legality of BUMDes and to improve legal understanding, (2) to increase the knowledge and skills of partners in good business management and business finance. and correct through the application of science and technology, and (3) To increase the role of BUMDes in community economic empowerment, so that the welfare of the community also increases. To achieve this goal, the service team prepares an activity plan that includes 4 (four) stages, namely stage 1 analysis of the situation and conditions of partners, stage 2 preparation and transfer of science and technology, stage 3 training and mentoring and stage 4 evaluation and program sustainability. By using the chronological method, the implementation of this activity resulted in an increase in Legal Knowledge and Understanding, an increase in partners' Knowledge and Skills regarding the Management and Finance of BUMDes by 83.33%.